2014
DOI: 10.1182/blood.v124.21.3453.3453
|View full text |Cite
|
Sign up to set email alerts
|

Oprozomib and Dexamethasone in Patients with Relapsed and/or Refractory Multiple Myeloma: Initial Results from the Dose Escalation Portion of a Phase 1b/2, Multicenter, Open-Label Study

Abstract: Background: Oprozomib (OPZ) is a selective oral proteasome inhibitor that binds selectively and irreversibly to its target. In a phase 1b/2 study of single-agent OPZ in patients (pts) with hematologic malignancies, OPZ has shown promising antitumor activity in pts with multiple myeloma (MM) (Savona, ASH 2012, 203; Kaufman, EHA 2013, P223; Ghobrial, ASH 2013, 3184). This multicenter, single arm phase 1b/2 study evaluates the safety and tolerability of OPZ with dexamethasone (DEX) in pts with relapsed and/or ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Major challenges related to tolerability were gastrointestinal, such as diarrhea, as well as frequent nausea and vomiting. However, none of the patients in this study demonstrated worsening of the basal, or a new neuropathy 46, 47…”
Section: New Proteasome Inhibitorsmentioning
confidence: 61%
“…Major challenges related to tolerability were gastrointestinal, such as diarrhea, as well as frequent nausea and vomiting. However, none of the patients in this study demonstrated worsening of the basal, or a new neuropathy 46, 47…”
Section: New Proteasome Inhibitorsmentioning
confidence: 61%
“…Efforts at developing oprozomib, an oral drug with structural similarities to carfilzomib, have met with difficulty, largely due to gastrointestinal toxicity. This has been observed in trials involving myeloma patients45 and patients with solid tumors 46…”
Section: Overview Of Current Treatment Approachesmentioning
confidence: 68%
“…56 In a similarly designed study combining OPZ with DEX enrolling 35 RRMM patients, the majority of which had prior BTZ exposure, ORR in the 2/7 was similarly measured at 35.5% whereas decreased treatment exposure was suggested as an explanation for a lesser response rate seen in the 5/14 arm. 57 While depth of response was greater in the first study, with several patients achieving ⩾VGPRs in contrast with the OPZ-DEX trial, this is likely related to heavier prior BTZ exposure in the OPZ-DEX study. GI toxicity appeared to be reduced with the addition of DEX.…”
Section: Future Directionsmentioning
confidence: 95%